Evogliptin prevents ceramide-induced pyroptosis during calcification via modulation of NLRP3/GSDM-D mediated pathway in Vascular Smooth Muscle Cells - Razia Rashid Rahil; Salman Shamas; Nissar Ahmad Wani; Neha Nanda; Sheikh Fayaz Ahmad; Sabry Mohamed Attia; Abid Hamid; Mohammad Afzal Zargar; Owais Mohmad Bhat (PLoS ONE, 2025)
Evogliptin, an anti-diabetic drug had positive impact on various cardiovascular events including inflammation and vascular calcification (VC), an active process driven by vascular smooth muscle cell (VSMC) phenotypic transition. Sphingolipids such as ceramide (CER) mediates inflammation and VC in the vascular tissue. We investigated whether evogliptin ameliorate phenotypic transition and pyroptosis in VSMCs as underlying cause of VC. In cultured VSMCs, isolated from the aorta of (C57/BL6) mouse, we observed more severe calcification with prior treatment of CER in P i -treated VSMCs as detected by Alizarin Red Staining. Prior CER- stimulation led to a marked upregulation of osteogenic markers such as RUNX2, OPN, BMP2 and decreased contractile markers SM22-α and α- SMA in P i -treated VSMCs as compared to control cells. In addition, increased expression of pyroptotic markers such as NLRP3, GSDM-D, IL-1 β , IL-18, and LDH release was observed with prior treatment of CER in P i -treated VSMCs as compared to control cells. Furthermore, MCC950 (NLRP3 inhibitor), disulfiram (GSDM-D inhibitor) and evogliptin significantly downregulated osteogenic and pyroptotic markers including LDH release in both P i ‐induced only and CER + P i -treated VSMCs. Moreover, GW4869 (SMase inhibitor) and evogliptin significantly reduced SMase activity in sphingomyelin (SM)-induced VSMCs as compared to both P i and SM only-treated groups. Also, the cleavage efficiency of GSDM-D was high in P i and CER + P i groups which was reduced with prior treatment of evogliptin. Hence, our data demonstrate that evogliptin alleviates VC by blocking phenotypic transition and associated pyroptosis via modulation of NLRP3/GSDM-D mediated pathway in CER-induced VSMCs.